An Analysis of Flouting Maxim in a Talk Show Program in Indonesia - Ismi Narulita Firda; Didin Nuruddin Hidayat; Alek Alek; Nurhalimah Nurhalimah (EDUVELOP, 2021)
This paper is a flouting maxim analysis in Sapa Indonesia Malam talk show at Kompas TV in which Jerinx or I Gede Ari Astina became a guest star in this talk show. The present study aims to analyze a conversation and dig out information about flouting maxims. The framework of analysis will use in the flouting Maxim of Grice’s Cooperative Principles (Geis et al., 1976). The flouting maxim has four maxims, and those are quality, quantity, relation, and manner. The method of this study was qualitative by using the utterances in the video conversation from the talk show in Sapa Indonesia Malam as analysis material, and the data were extracted from the video. This study's instrument was the transcript text of the utterances between the hosts and Jerinx as a guest star consisting of flouting maxims. The data were analyzed by using flouting of the maxim in Discourse Analysis’ concept. This paper attempts to investigate the flouting maxims that mostly appear in the video conversation and determine the cause or reason for the maxim to emerge. The researchers comprehended the types of flouting maxims in the talk show, and then the researchers determined the types selected into categories based on guests' utterances. After that, the researchers analyzed the predetermined types. The study found some floutings of the maxims of relation. There were 50% maxims of relation flouted by speakers, and from nine flouting maxims, the four data had the most reasons for appearing in the conversation.